A process for recycling waste rubber magnetic and application thereof

The physical recycling process, which involves mixing and surface modification, solves the problems of low rubber magnetic recycling efficiency and pollution caused by microwave desulfurization, achieving efficient and environmentally friendly rubber magnetic regeneration and improving product compatibility and flexibility.

CN117549462BActive Publication Date: 2026-11-06HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210938899.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-05
Publication Date
2026-11-06
Estimated Expiration
2042-08-05

AI Technical Summary

Technical Problem

Existing magnetic rubber recycling methods are inefficient and environmentally unfriendly, and microwave desulfurization can easily lead to carbonization of rubber powder and a decline in product quality.

Method used

A physical mixing process is used to replace microwave desulfurization. Rubber magnets are recovered through mixing, preliminary crushing, and grinding. The ferrite magnetic powder is then surface-modified to produce halogen-free or lead-free products.

Benefits of technology

It improves the efficiency of rubber magnetic recovery, avoids the carbonization of rubber powder, ensures product performance and does not generate pollution, and at the same time improves the compatibility of ferrite magnetic powder with rubber and the flexibility of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003784686240000081
    Figure BDA0003784686240000081
Patent Text Reader

Abstract

The present application relates to the field of magnetic material recycling, and aims at the problems of low recycling efficiency and environmental pollution of magnetic rubber, and provides a waste rubber magnetic recycling process and application thereof.The recycling process comprises the following steps: waste rubber magnetic is subjected to internal mixing, the mixed material is preliminarily crushed, then is crushed by grinding to obtain recycled material, and the unqualified material is returned to the grinding process.The waste rubber magnetic is a side material generated in the production of products after high-temperature vulcanization and setting.The internal mixing is used to replace other desulfurization steps such as microwave desulfurization, carbonization of rubber powder is avoided, the performance of the waste rubber magnetic recycled material is ensured, and pollution is not generated.The application of the recycled material obtained by the waste rubber magnetic recycling process is also provided, and the recycled material is used to prepare halogen-free products or lead-free products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic material recycling, and in particular to a recycling process for waste rubber magnets and its application. Background Technology

[0002] Rubber magnets are a type of ferrite magnetic material, made by bonding ferrite magnetic powder with synthetic rubber and then processing it through extrusion molding, calendering, injection molding, and other processes. They possess flexibility, elasticity, and the ability to be twisted. They can be processed into strips, rolls, sheets, blocks, rings, and various complex shapes. The expanding applications of rubber magnets have also increased the quantity of waste rubber magnets. With increasing environmental awareness, growing environmental demands, and rising production costs, the recycling of rubber magnets requires a low-cost, high-value-added technological approach.

[0003] Current conventional rubber recycling methods include adding plasticizers, low-temperature pulverization, and microwave heating desulfurization and regeneration. Among these, adding plasticizers results in low efficiency in producing regenerated rubber, and low-temperature pulverization is costly. Furthermore, it does not fully utilize the magnetic properties of rubber magnets and is only suitable for use in products with low performance and quality requirements, resulting in low recycling value. Microwave heating desulfurization can easily cause a large amount of energy to accumulate in the middle part of the rubber magnet, which can easily lead to partial carbonization of the rubber powder, resulting in a lot of bubbles and impurities in the regenerated rubber magnet. Patent CN112280096A discloses a regenerated rubber magnet, its preparation method, and its application. The preparation method of the regenerated rubber magnet includes the following steps: (1) mixing waste rubber magnets with ferrite magnetic powder and then performing a first mixing; (2) performing a first microwave desulfurization on the material after the first mixing; (3) performing a second mixing on the material after the first microwave desulfurization; (4) performing a second microwave desulfurization on the material after the second mixing to obtain a desulfurized ferrite-containing rubber magnet; (5) adding rubber and rubber additives to the desulfurized ferrite-containing rubber magnet and then performing a second mixing. The recycled rubber magnets prepared by this invention possess excellent magnetic and physical properties, while avoiding rubber powder carbonization. The surface is smooth and free of impurities, achieving the magnetic, physical, and surface properties of conventional rubber magnets. However, microwave desulfurization of the rubber magnets will produce slight pollution. Summary of the Invention

[0004] To overcome the problems of low efficiency and environmental unfriendliness in rubber magnet recycling, this invention provides a recycling process for waste rubber magnets and its application. This invention recycles rubber magnets using only physical methods, with simpler steps and higher efficiency compared to existing technologies. Furthermore, the recycled rubber magnets contain fewer impurities, thus not affecting their secondary use.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A recycling process for waste rubber magnets includes the following steps: the waste rubber magnets are subjected to intensive mixing; the mixed material is first pre-crushed, then further crushed and ground to obtain recycled material; unprocessed material is returned for regrinding. The waste rubber magnets are scrap materials generated during product manufacturing after high-temperature vulcanization and shaping. This invention uses intensive mixing to replace other desulfurization steps such as microwave desulfurization, avoiding rubber powder carbonization, ensuring the performance of the recycled waste rubber magnets, and preventing pollution.

[0006] Preferably, the mixing temperature is 120-130℃ and the time is 10-12 minutes.

[0007] Preferably, the material is crushed and then passed through a sieve with a 1-4 mm aperture, or ground and crushed and then passed through a sieve with a 0.1-0.3 mm aperture.

[0008] This invention also provides the application of recycled materials obtained from the recycling process of waste rubber magnets for the preparation of halogen-free or lead-free products.

[0009] Preferably, the preparation of the halogen-free product includes the following steps: 1) By weight, mix 45-65 parts of ferrite magnetic powder, 4-8 parts of rubber, 30-50 parts of the recycled material, 0.1-0.3 parts of stearic acid, 0.05-0.1 parts of vulcanizing agent, 0.1-0.3 parts of epoxidized soybean oil, and 0.05-0.2 parts of phthalate, and then mix them at 130-140℃. 2) The finished product is crushed and sheeted to a thickness of 1.4-1.5 mm, then stacked and rolled into thin sheets; 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 160-180℃ and a vulcanization time of 5-8 minutes.

[0010] Preferably, the preparation of the lead-free product includes the following steps: 1) By weight, mix 60-65 parts of ferrite magnetic powder, 6-8 parts of chlorinated polyethylene, 35-40 parts of the recycled material, 0.3-0.5 parts of calcium stearate, 0.2-0.3 parts of epoxy plasticizer, and 0.1-0.2 parts of phthalate, and then mix them at 120-130°C. 2) After the internal mixing is completed, the material is crushed and sheeted with a sheet thickness of 1.4-1.5mm. The sheets are then stacked and rolled into thin sheets to prepare lead-free products.

[0011] Preferably, the ferrite magnetic powder undergoes the following treatment: (1) Mix aminosilane and ferrite magnetic powder and ball mill to obtain surface-modified magnetic powder. Disperse the surface-modified magnetic powder in water, adjust the pH to 10-12, heat to 40-60℃, and add propyl glycidyl ether dropwise while stirring. After the addition is complete, raise the temperature to 70-80℃ and react for 4-6 hours to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) is mixed with castor oil and methyl methacrylate, dispersed evenly, and reacted in an organic solvent at 80-90℃ for 10-12h to obtain surface-coated magnetic powder.

[0012] This invention processes ferrite magnetic powder. First, the ferrite magnetic powder is modified with aminosilane to impart amino groups to its surface. Then, through the epoxy addition reaction of the amino groups with propyl glycidyl ether, unsaturated carbon-carbon double bonds are introduced onto the surface of the ferrite magnetic powder. Next, the carbon-carbon double bonds are copolymerized with castor oil and methyl methacrylate. Finally, several long chains are grafted onto the surface of the resulting ferrite magnetic powder. These long chains intertwine, effectively coating the ferrite magnetic powder. Furthermore, the castor oil contains multiple hydroxyl groups. The surface-coated magnetic powder prepared using the above method has a large space for free rotation and mobility of the long chains on its surface. On the one hand, it has good fluidity and good compatibility and dispersibility when mixed with components such as rubber or chlorinated polyethylene. On the other hand, the presence of flexible ether bonds improves the flexibility of the resulting product.

[0013] Preferably, the mass ratio of aminosilane to ferrite magnetic powder in step (1) is (1-3):100.

[0014] Preferably, the molar ratio of propyl glycidyl ether to ferrite magnetic powder in step (1) is (5-8):1.

[0015] Preferably, the mass ratio of grafted magnetic powder, castor oil and methyl methacrylate in step (2) is 1:(8-10):(1-3).

[0016] Therefore, the beneficial effects of the present invention are: (1) replacing microwave desulfurization and other desulfurization steps with internal mixing, avoiding carbonization of rubber powder, ensuring the performance of waste rubber magnetic recycling material, and not generating pollution; (2) the long chains on the surface of the prepared ferrite magnetic powder have a large free rotation space and mobility. On the one hand, it has good fluidity and good compatibility and dispersibility when mixed with rubber or chlorinated polyethylene and other components; on the other hand, the presence of flexible ether bonds can improve the flexibility of the product. Detailed Implementation

[0017] The technical solution of the present invention will be further described below through specific embodiments.

[0018] In this invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the field. The methods in the embodiments, unless otherwise specified, are conventional methods in the field.

[0019] General Implementation Examples A recycling process for waste rubber magnets includes the following steps: the waste rubber magnets are internally mixed at a temperature of 120-130℃ for 10-12 minutes; the mixed material is first initially crushed using a pulverizer and passed through a sieve with a 1-4mm aperture; then the initially crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a vibrating screen with a 0.1-0.3mm aperture for screening and filtration to obtain recycled material, requiring 100% pass-through; the unpassed material is returned for regrinding.

[0020] The recycled materials obtained from the waste rubber magnet recycling process can be used to prepare halogen-free or lead-free products.

[0021] The preparation of the halogen-free product includes the following steps: 1) By weight, mix 45-65 parts of ferrite magnetic powder, 4-8 parts of rubber, 30-50 parts of the recycled material, 0.1-0.3 parts of stearic acid, 0.05-0.1 parts of vulcanizing agent, 0.1-0.3 parts of epoxidized soybean oil, and 0.05-0.2 parts of phthalate, and then mix them at 130-140℃. 2) The finished product is crushed and sheeted to a thickness of 1.4-1.5 mm, then stacked and rolled into thin sheets; 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 160-180℃ and a vulcanization time of 5-8 minutes.

[0022] The preparation of the lead-free product includes the following steps: 1) By weight, mix 60-65 parts of ferrite magnetic powder, 6-8 parts of chlorinated polyethylene, 35-40 parts of the recycled material, 0.3-0.5 parts of calcium stearate, 0.2-0.3 parts of epoxy plasticizer, and 0.1-0.2 parts of phthalate, and then mix them at 120-130°C. 2) After the internal mixing is completed, the material is crushed and sheeted with a sheet thickness of 1.4-1.5mm. The sheets are then stacked and rolled into thin sheets to prepare lead-free products.

[0023] Preferably, the ferrite magnetic powder undergoes the following treatment: (1) Mix aminosilane and ferrite magnetic powder and ball mill to obtain surface-modified magnetic powder. The mass ratio of aminosilane to ferrite magnetic powder is (1-3):100. Disperse the surface-modified magnetic powder in water, adjust the pH to 10-12, heat to 40-60℃, and add propyl glycidyl ether dropwise while stirring. The molar ratio of propyl glycidyl ether to ferrite magnetic powder is (5-8):1. After the addition is complete, heat to 70-80℃ and react for 4-6 hours to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) is mixed with castor oil and methyl methacrylate in a mass ratio of 1:(8-10):(1-3), dispersed evenly, and reacted in an organic solvent at 80-90℃ for 10-12h to obtain surface-coated magnetic powder.

[0024] Example 1 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0025] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 62.2 parts of ferrite magnetic powder, 6.2 parts of nitrile rubber, 31.1 parts of the recycled material, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0026] Example 2 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0027] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 45 parts of ferrite magnetic powder, 4.5 parts of nitrile rubber, 50 parts of the recycled material, 0.15 parts of stearic acid, 0.08 parts of vulcanizing agent (BIPB), 0.12 parts of epoxidized soybean oil, and 0.08 parts of phthalate are mixed and kneaded at 132°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0028] Example 3 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0029] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 62.2 parts of ferrite magnetic powder coated with silica aerogel, 6.2 parts of nitrile rubber, 31.1 parts of recycled material coated with silica aerogel, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0030] The ferrite magnetic powder undergoes the following treatment: (1) Ferrite magnetic powder was dispersed in anhydrous ethanol to obtain a dispersion with a solid content of 400 g / L. Aminosilane was added, and the mass ratio of ferrite magnetic powder to aminosilane was 100:(1-3). The mixture was ball-milled for 4 h to obtain a slurry. The slurry was filtered and separated. The solid phase was placed in a blower dryer and dried at 60 °C to obtain surface-modified ferrite magnetic powder. The surface-modified magnetic powder was dispersed in water, and the pH was adjusted to 11 with 1 mol / L sodium hydroxide solution. The mixture was heated to 60 °C, and propyl glycidyl ether was added dropwise while stirring. The molar ratio of propyl glycidyl ether to ferrite magnetic powder was 7:1. After the addition was completed, the temperature was raised to 80 °C and reacted for 4 h. The reaction solution was filtered, washed, and dried to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) is mixed with castor oil and methyl methacrylate in a mass ratio of 1:9:2, dispersed evenly, and reacted in an organic solvent at 80°C for 12 hours to obtain surface-coated magnetic powder.

[0031] Example 4 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at 120°C for 12 minutes; the mixed material is first crushed using a pulverizer and passed through a 1 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0032] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare lead-free products. The steps are as follows: 1) By mass, 60 parts of ferrite magnetic powder, 7 parts of chlorinated polyethylene, 38 parts of the recycled material, 0.4 parts of calcium stearate, 0.2 parts of epoxy plasticizer, and 0.1 parts of phthalate are mixed and kneaded at 130°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 2mm; then it is calendered to produce sheets with a thickness of 1.5mm; the 6-layer stack is calendered into 3mm sheets.

[0033] Comparative Example 1 The preparation steps of a halogen-free product are as follows: 1) By mass, mix 90 parts of ferrite magnetic powder, 9 parts of nitrile rubber, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate, and then mix them at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0034] This comparative example did not use recycled materials to demonstrate the impact of using recycled materials on the performance of halogen-free products. Since the ratio of rubber to magnetic powder in existing rubber magnets is approximately 1:10, this comparative example roughly converts the recycled material 31.1 from Example 1 into 3 parts rubber + 30 parts magnetic powder, supplementing the amounts of ferrite magnetic powder and nitrile rubber.

[0035] Comparative Example 2 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0036] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 27 parts of ferrite magnetic powder, 2.7 parts of nitrile rubber, 70 parts of the recycled material, 0.15 parts of stearic acid, 0.08 parts of vulcanizing agent (BIPB), 0.12 parts of epoxidized soybean oil, and 0.08 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0037] Comparative Example 3 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0038] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 62.2 parts of ferrite magnetic powder coated with silica aerogel, 6.2 parts of nitrile rubber, 31.1 parts of recycled material coated with silica aerogel, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0039] The ferrite magnetic powder is processed as follows: the ferrite magnetic powder is dispersed in anhydrous ethanol to obtain a dispersion with a solid content of 400 g / L, aminosilane is added, the mass ratio of ferrite magnetic powder to aminosilane is 100:(1-3), ball milling is performed for 4 hours to obtain a slurry, the slurry is filtered and separated, and the solid phase is placed in a blower dryer and dried at 60°C to obtain surface-modified ferrite magnetic powder.

[0040] Comparative Example 4 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0041] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 62.2 parts of ferrite magnetic powder coated with silica aerogel, 6.2 parts of nitrile rubber, 31.1 parts of recycled material coated with silica aerogel, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0042] The ferrite magnetic powder was processed as follows: ferrite magnetic powder was dispersed in anhydrous ethanol to obtain a dispersion with a solid content of 400 g / L. Aminosilane was added, with a mass ratio of ferrite magnetic powder to aminosilane of 100:(1-3). The mixture was ball-milled for 4 hours to obtain a slurry. The slurry was filtered and separated, and the solid phase was placed in a forced-air dryer and dried at 60°C to obtain surface-modified ferrite magnetic powder. The surface-modified magnetic powder was dispersed in water, and the pH was adjusted to 11 with 1 mol / L sodium hydroxide solution. The mixture was heated to 60°C, and propyl glycidyl ether was added dropwise while stirring. The molar ratio of propyl glycidyl ether to ferrite magnetic powder was 7:1. After the addition was complete, the temperature was raised to 80°C and reacted for 4 hours. The reaction solution was filtered, washed, and dried to obtain grafted magnetic powder.

[0043] Comparative Example 5 A recycling process for waste rubber magnets includes the following steps: 5 kg of waste rubber magnets are mixed in an intensive mixing process at a temperature of 125℃ for 10.5 min; the mixed material is first crushed using a pulverizer and passed through a 2.5 mm mesh screen; then the crushed material is ground and crushed using a grinding mill; the ground and crushed material is then poured into a 120 mesh vibrating screen for screening and filtration, requiring 100% pass-through; the unpassed material is returned for regrinding to obtain recycled material with a particle size of 0.1-0.13 mm.

[0044] The above-mentioned recycled material obtained from the waste rubber magnet recycling process is used to prepare halogen-free products. The steps are as follows: 1) By mass, 62.2 parts of ferrite magnetic powder coated with silica aerogel, 6.2 parts of nitrile rubber, 31.1 parts of recycled material coated with silica aerogel, 0.1-0.3 parts of stearic acid, 0.1 parts of vulcanizing agent (BIPB), 0.2 parts of epoxidized soybean oil, and 0.1 parts of phthalate are mixed and kneaded at 133°C. 2) After the internal mixing is completed, the material is crushed to a particle size of 1.5-3.5mm; then it is calendered to produce sheets with a thickness of 1.4mm; the 6-layer stack is calendered into 3mm thin sheets using a calender. 3) Prepare halogen-free products by vulcanizing the thin sheets at a temperature of 165℃ and a vulcanization time of 6min.

[0045] The ferrite magnetic powder undergoes the following treatment: (1) Ferrite magnetic powder was dispersed in anhydrous ethanol to obtain a dispersion with a solid content of 400 g / L. Aminosilane was added, and the mass ratio of ferrite magnetic powder to aminosilane was 100:(1-3). The mixture was ball-milled for 4 h to obtain a slurry. The slurry was filtered and separated. The solid phase was placed in a blower dryer and dried at 60 °C to obtain surface-modified ferrite magnetic powder. The surface-modified magnetic powder was dispersed in water, and the pH was adjusted to 11 with 1 mol / L sodium hydroxide solution. The mixture was heated to 60 °C, and propyl glycidyl ether was added dropwise while stirring. The molar ratio of propyl glycidyl ether to ferrite magnetic powder was 7:1. After the addition was completed, the temperature was raised to 80 °C and reacted for 4 h. The reaction solution was filtered, washed, and dried to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) and castor oil are mixed at a mass ratio of 1:9, dispersed evenly, and reacted in an organic solvent at 80°C for 12 hours to obtain surface-coated magnetic powder.

[0046] Performance testing The halogen-free / lead-free products obtained in Examples 1-4 and Comparative Examples 1-2 were cut into 50mm×50mm samples for testing of physical and magnetic properties. The results are shown in Table 1.

[0047] Table 1 Compared with Comparative Example 1, Examples 1-4 show only a slight decrease in magnetic properties and excellent physical properties, indicating that the recycled material obtained using the waste rubber magnet recycling process of this invention can be fully used to prepare products. Comparing Examples 1 and 2 with Comparative Example 2, within the preferred range, the magnetic and physical properties of the product gradually decrease with the increase of the amount of recycled material. In Comparative Example 2, the amount of recycled material was as high as 79 parts, which led to cracking of the product. Therefore, it is necessary to control the proportion of recycled material added to ensure the excellent performance of the product.

[0048] 2. The halogen-free products obtained in Examples 1, 3 and Comparative Examples 3-5 were subjected to flexibility tests (the test specimens were 100mm × 10mm × 2mm in size). The results are shown in Table 2.

[0049] Table 2 project Example 1 Example 3 Comparative Example 3 Comparative Example 4 Comparative Example 5 Tensile strength (MPa) 6.4 8.7 6.6 7.5 8.0 Elongation at break % 151 186 155 170 179 Compared to Example 1, Example 3 involved coating the ferrite magnetic powder. As shown in Tables 1 and 2, Example 3 improved the product's toughness without affecting its magnetic properties. Compared to Example 3, Comparative Example 3 only modified the ferrite magnetic powder surface with aminosilane, resulting in minimal improvement in product toughness. Comparative Example 4 only modified the ferrite magnetic powder surface with aminosilane and grafted it with propyl glycidyl ether, resulting in shorter chain segments that were difficult to form entanglement and coating, thus offering little improvement in product toughness. Comparative Example 5 did not include methyl methacrylate in the copolymerization reaction, leading to a less significant improvement in product toughness compared to Example 3. Therefore, Comparative Examples 3-5 demonstrate that all modification steps of the ferrite magnetic powder in this invention are indispensable, and the combined effect of all components yields a product with excellent toughness.

[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. An application of a recycling process for waste rubber magnets, characterized in that, The recycling process of waste rubber magnets includes the following steps: the waste rubber magnets are mixed in an intensive manner, the mixed material is first crushed and then ground to obtain recycled material, and the unprocessed material is returned to regrinding. Using recycled materials to produce lead-free products includes the following steps: 1) By weight, mix 60-65 parts of ferrite magnetic powder, 6-8 parts of chlorinated polyethylene, 35-40 parts of the recycled material, 0.3-0.5 parts of calcium stearate, 0.2-0.3 parts of epoxy plasticizer, and 0.1-0.2 parts of phthalate, and then mix them at 120-130 ℃. 2) After the internal mixing is completed, the material is crushed and sheeted with a sheet thickness of 1.4-1.5 mm. The sheets are then stacked and rolled into thin sheets to prepare lead-free products. The ferrite magnetic powder undergoes the following treatment: (1) Mix aminosilane and ferrite magnetic powder and ball mill to obtain surface-modified magnetic powder. Disperse the surface-modified magnetic powder in water, adjust the pH to 10-12, heat to 40-60 ℃, and add propyl glycidyl ether dropwise while stirring. After the addition is complete, raise the temperature to 70-80 ℃ and react for 4-6 h to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) is mixed with castor oil and methyl methacrylate, dispersed evenly, and reacted in an organic solvent at 80-90 °C for 10-12 h to obtain surface-coated magnetic powder.

2. The application of the waste rubber magnet recycling process according to claim 1, characterized in that, In step (1), the mass ratio of aminosilane to ferrite magnetic powder is (1-3):

100.

3. The application of the waste rubber magnet recycling process according to claim 1 or 2, characterized in that, In step (1), the molar ratio of propyl glycidyl ether to ferrite magnetic powder is (5-8):

1.

4. The application of the waste rubber magnet recycling process according to claim 1, characterized in that, In step (2), the mass ratio of grafted magnetic powder, castor oil and methyl methacrylate is 1:(8-10):(1-3).

5. The application of the waste rubber magnet recycling process according to claim 1, characterized in that, The mixing temperature is 120-130 ℃ and the time is 10-12 min; After initial crushing, the material passes through a sieve with a 1-4 mm aperture; after grinding and crushing, it passes through a sieve with a 0.1-0.3 mm aperture.

6. The application of a recycling process for waste rubber magnets, characterized in that, The recycling process of waste rubber magnets includes the following steps: the waste rubber magnets are mixed in an intensive manner, the mixed material is first crushed and then ground to obtain recycled material, and the unprocessed material is returned to regrinding. Using recycled materials to prepare halogen-free products includes the following steps: 1) By weight, mix 45-65 parts of ferrite magnetic powder, 4-8 parts of rubber, 30-50 parts of the recycled material, 0.1-0.3 parts of stearic acid, 0.05-0.1 parts of vulcanizing agent, 0.1-0.3 parts of epoxidized soybean oil, and 0.05-0.2 parts of phthalate, and then perform intensive mixing at 130-140 ℃; 2) The finished product is crushed and sheeted to a thickness of 1.4-1.5 mm, then stacked and rolled into thin sheets; 3) Prepare halogen-free products by vulcanizing thin sheets at a temperature of 160-180 ℃ and a vulcanization time of 5-8 min; The ferrite magnetic powder undergoes the following treatment: (1) Mix aminosilane and ferrite magnetic powder and ball mill to obtain surface-modified magnetic powder. Disperse the surface-modified magnetic powder in water, adjust the pH to 10-12, heat to 40-60 ℃, and add propyl glycidyl ether dropwise while stirring. After the addition is complete, raise the temperature to 70-80 ℃ and react for 4-6 h to obtain grafted magnetic powder. (2) The grafted magnetic powder obtained in step (1) is mixed with castor oil and methyl methacrylate, dispersed evenly, and reacted in an organic solvent at 80-90 °C for 10-12 h to obtain surface-coated magnetic powder.

7. The application of the waste rubber magnet recycling process according to claim 6, characterized in that, In step (1), the mass ratio of aminosilane to ferrite magnetic powder is (1-3):

100.

8. The application of the waste rubber magnet recycling process according to claim 6 or 7, characterized in that, In step (1), the molar ratio of propyl glycidyl ether to ferrite magnetic powder is (5-8):

1.

9. The application of the waste rubber magnet recycling process according to claim 6, characterized in that, In step (2), the mass ratio of grafted magnetic powder, castor oil and methyl methacrylate is 1:(8-10):(1-3).

10. The application of the waste rubber magnet recycling process according to claim 6, characterized in that, The mixing temperature is 120-130 ℃ and the time is 10-12 min; After initial crushing, the material passes through a sieve with a 1-4 mm aperture; after grinding and crushing, it passes through a sieve with a 0.1-0.3 mm aperture.

Citation Information

Patent Citations

  • Regenerated rubber magnet and preparation method and application thereof

    CN112280096A

  • Preparation method of rubber-plastic soft-magnetism antifreeze plate for wireless charging

    CN105985583A

  • Ferrite magnetic rubber magnetic powder recovery method

    CN110126132A

  • Rubber magnetic particle material for injection molding and preparation method thereof

    CN112175308A